Nitrogen-doped graphite material, electrode, electrochemical device, and electronic device comprising the same
Patent Information
- Application Number
- CN202611236535.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
然而,基于石墨负极的锂离子二次电池等电化学装置体系,其能量密度、快充能力提升空间日趋收窄,已难以满足终端应用场景对更高能量输出、更高使用倍率的迫切需求
本申请的氮掺杂石墨材料通过控制0.70≤La/Lc≤2.40同时提高了锂离子二次电池等电化学装置的能量密度和快充性能,以及降低了锂离子二次电池等电化学装置的循环膨胀。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of energy storage technology, and more specifically, to nitrogen-doped graphite materials, electrodes, electrochemical devices, and electronic devices comprising the same. Background Technology
[0002] Graphite anodes have become the mainstream choice for electrochemical devices such as lithium-ion rechargeable batteries due to their high theoretical specific capacity (372 mAh / g), stable layered structure, and mature industrial applications. However, the potential for improving the energy density and fast charging capability of electrochemical devices such as lithium-ion rechargeable batteries based on graphite anodes is increasingly limited, making it difficult to meet the urgent needs of end-user applications for higher energy output and higher utilization rates.
[0003] For graphite anode systems, existing methods for improving the energy density of electrochemical devices such as lithium-ion secondary batteries often inevitably exacerbate the thickness expansion of the electrochemical device during cycling, thus reducing the fast-charging performance of the electrochemical device.
[0004] Therefore, there is an urgent need to develop a nitrogen-doped graphite material to simultaneously improve the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of such devices. Summary of the Invention
[0005] The purpose of this application is to address the shortcomings of the prior art by providing nitrogen-doped graphite materials, electrodes, electrochemical devices, and electronic devices comprising the same.
[0006] To achieve the above objectives, this application provides a nitrogen-doped graphite material, wherein the nitrogen-doped graphite material comprises graphite and a nitrogen-doped carbon layer is disposed on the surface of the graphite; The nitrogen-doped graphite material has a crystallite size of La in the a-axis direction and a crystallite size of Lc in the c-axis direction, with 0.70≤La / Lc≤2.40.
[0007] The nitrogen-doped graphite material of this application improves the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries by controlling 0.70≤La / Lc≤2.40, while reducing the cyclic expansion of such electrochemical devices.
[0008] Specifically, when La / Lc is too small (<0.70), it indicates that the length La of the crystallites in the a-axis direction of the nitrogen-doped graphite material is insufficient relative to the thickness Lc in the c-axis direction. The nitrogen-doped graphite material tends to be isotropic, which is beneficial to reduce the lattice stress caused by anisotropic expansion during lithium ion insertion / extraction, thereby suppressing the cyclic expansion of the electrochemical device and improving the fast charging performance of the electrochemical device. However, a small La means that the graphite basal surface (i.e. the main active site for lithium ion storage) is not fully developed and the degree of graphitization is low, which leads to a decrease in the reversible capacity and compaction density of the nitrogen-doped graphite material, making it difficult to meet the high energy density requirements of the electrochemical device.
[0009] Conversely, when La / Lc is too large (>2.40), it indicates that the microcrystals of nitrogen-doped graphite material have grown excessively in the a-axis direction, and the graphite basal plane size La is significantly larger than the stack thickness Lc, exhibiting strong anisotropy. Although this is beneficial to improving the graphitization degree and lithium storage capacity of nitrogen-doped graphite material, thereby improving the reversible capacity and compaction density of nitrogen-doped graphite material, and thus improving the energy density of electrochemical device, during the lithium ion insertion / extraction process, the graphite sheets of nitrogen-doped graphite material undergo violent and uneven expansion along the c-axis direction, resulting in large internal stress and microcracks inside the particles of nitrogen-doped graphite material, which in turn significantly increases the cyclic expansion of electrochemical device. At the same time, an excessively large La will prolong the path of lithium ions diffusing from the particle edge to the deep interlayer, increase the lithium ion transport resistance, and deteriorate the fast charging performance of electrochemical device.
[0010] When the La / Lc ratio is controlled within the range of 0.70 to 2.40, on the one hand, a moderate amount of La ensures sufficient development of the graphite matrix, improving the graphitization degree and interlayer lithium storage capacity of nitrogen-doped graphite materials, thereby increasing the reversible capacity and compaction density of nitrogen-doped graphite materials, and consequently improving the energy density of electrochemical devices. On the other hand, a moderately restricted La ratio does not excessively dominate Lc, keeping the microcrystalline anisotropy of nitrogen-doped graphite materials at an acceptable level. This shortens the solid-phase diffusion distance of lithium ions (which is beneficial for lithium ion transport) and suppresses excessive volume expansion along the c-axis during lithium intercalation, thus significantly reducing the cycle expansion of electrochemical devices and improving their fast-charging performance. Therefore, this application achieves an excellent balance between energy density, fast-charging performance, and cycle expansion in electrochemical devices such as lithium-ion secondary batteries by precisely controlling the La / Lc ratio.
[0011] In some implementations, 35nm ≤ La ≤ 60nm.
[0012] In some implementations, 25nm ≤ Lc ≤ 45nm.
[0013] In some implementations, 1.10 ≤ La / Lc ≤ 2.00.
[0014] In some embodiments, the full width at half maximum (FWHM) of the (110) crystal plane of the nitrogen-doped graphite material obtained by X-ray diffraction (XRD) is 0.16°-0.29°.
[0015] In some embodiments, the full width at half maximum (FWHM) of the (002) crystal plane obtained by X-ray diffraction (XRD) of the nitrogen-doped graphite material is 0.17°-0.33°.
[0016] In some embodiments, the nitrogen element in the nitrogen-doped graphite material includes graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen. Based on the total mass of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen, the mass percentage of graphitic nitrogen is A, the mass percentage of pyridine nitrogen is B, and the mass percentage of pyrrole nitrogen is C, with 0.40 ≤ A / (B+C) ≤ 2.30.
[0017] In some implementations, 0.90 ≤ A / (B+C) ≤ 1.75.
[0018] The introduction of graphitic nitrogen does not significantly disrupt the carbon six-membered ring structure between graphite layers in nitrogen-doped graphite materials, thus protecting the fast-charging performance of electrochemical devices and reducing cycle expansion. Pyrrole nitrogen and pyridine nitrogen can provide additional lithium storage sites, which is beneficial to improving the energy density of electrochemical devices. By controlling the range of values for A / (B+C), this application can further improve the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as further reduce the cycle expansion of electrochemical devices such as lithium-ion secondary batteries.
[0019] In some implementations, 0.25 ≤ A ≤ 0.75.
[0020] In some implementations, 0.30 ≤ A ≤ 0.70.
[0021] In some implementations, 0.07 ≤ B ≤ 0.40.
[0022] In some implementations, 0.10 ≤ B ≤ 0.35.
[0023] In some implementations, 0.07 ≤ C ≤ 0.40.
[0024] In some implementations, 0.10 ≤ C ≤ 0.35.
[0025] In some embodiments, the average particle size Dv50 of the nitrogen-doped graphite material is D1, where 7 μm ≤ D1 ≤ 15 μm.
[0026] In some implementations, 8μm≤D1≤14μm.
[0027] In some implementations, 10μm≤D1≤12μm.
[0028] In some embodiments, the nitrogen-doped graphite material has an average thickness of D2, where 50 nm ≤ D2 ≤ 450 nm.
[0029] In some implementations, 100nm ≤ D2 ≤ 400nm.
[0030] In some implementations, 200nm ≤ D2 ≤ 360nm.
[0031] In some embodiments, the mass percentage of nitrogen is 0.01%-0.5% based on the mass of the nitrogen-doped graphite material.
[0032] This application provides an electrode comprising the nitrogen-doped graphite material described above.
[0033] In some embodiments, the electrode is a negative electrode.
[0034] This application provides an electrochemical device including the electrodes described above.
[0035] This application also provides an electronic device that includes the electrochemical device described above.
[0036] Compared with the prior art, the beneficial effects of this application are as follows: The nitrogen-doped graphite material of this application improves the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries by controlling 0.70≤La / Lc≤2.40, while reducing the cyclic expansion of such electrochemical devices.
[0037] Specifically, when La / Lc is too small (<0.7), it indicates that the length La of the crystallites in the a-axis direction of the nitrogen-doped graphite material is insufficient relative to the thickness Lc in the c-axis direction. The nitrogen-doped graphite material tends to be isotropic, which is beneficial to reduce the lattice stress caused by anisotropic expansion during lithium ion insertion / extraction, thereby suppressing the cyclic expansion of the electrochemical device and improving the fast charging performance of the electrochemical device. However, an excessively small La means that the graphite basal surface (i.e. the main active site for lithium ion storage) is not fully developed and the degree of graphitization is low, resulting in a decrease in the reversible capacity and compaction density of the nitrogen-doped graphite material, making it difficult to meet the high energy density requirements of the electrochemical device.
[0038] Conversely, when La / Lc is too large (>2.4), it indicates that the microcrystals of nitrogen-doped graphite material have grown excessively in the a-axis direction, and the graphite basal plane size La is significantly larger than the stack thickness Lc, exhibiting strong anisotropy. Although this is beneficial to improving the graphitization degree and lithium storage capacity of nitrogen-doped graphite material, thereby improving the reversible capacity and compaction density of nitrogen-doped graphite material, and thus improving the energy density of electrochemical device, during the lithium ion insertion / extraction process, the graphite sheets of nitrogen-doped graphite material undergo violent and uneven expansion along the c-axis direction, resulting in large internal stress and microcracks inside the particles of nitrogen-doped graphite material, which in turn significantly increases the cyclic expansion of electrochemical device. At the same time, an excessively large La will prolong the path of lithium ions diffusing from the particle edge to the deep interlayer, increase the lithium ion transport resistance, and deteriorate the fast charging performance of electrochemical device.
[0039] When the La / Lc ratio is controlled within the range of 0.7 to 2.4, on the one hand, a moderate amount of La ensures sufficient development of the graphite matrix, improving the graphitization degree and interlayer lithium storage capacity of nitrogen-doped graphite materials, thereby increasing the reversible capacity and compaction density of nitrogen-doped graphite materials, and consequently improving the energy density of electrochemical devices. On the other hand, a moderately restricted La ratio does not excessively dominate Lc, keeping the microcrystalline anisotropy of nitrogen-doped graphite materials at an acceptable level. This shortens the solid-phase diffusion distance of lithium ions (which is beneficial for lithium ion transport) and suppresses excessive volume expansion along the c-axis during lithium intercalation, thus significantly reducing the cycle expansion of electrochemical devices and improving their fast-charging performance. Therefore, this application achieves an excellent balance between energy density, fast-charging performance, and cycle expansion in electrochemical devices such as lithium-ion secondary batteries by precisely controlling the La / Lc ratio. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0041] <General Definition> The term "average particle size Dv50" refers to the particle size value that corresponds to a cumulative volume fraction of 50% in a particle group.
[0042] The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.
[0043] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0044] In this application, a list of items connected by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0045] In the following description, all figures disclosed in this application are approximate values, regardless of whether the terms "about" or "approximately" are used in conjunction. They may vary by 1%, 2%, 5%, or sometimes 10% to 20%. Whenever a range of values with a lower limit (RL) and an upper limit (RU) is disclosed, any values falling within that range are specifically disclosed. Specifically, the following values within this range are specifically disclosed: R = RL + k * (RU - RL), where k is a variable with a 1% increment from 1% to 100%, i.e., k is 1%, 2%, 3%, 4%, 5%, ..., 50%, 51%, 52%, ..., 95%, 96%, 97%, 98%, 99%, or 100%. Furthermore, any range of values defined by the two R values as defined above are also specifically disclosed.
[0046] In this application, numerical ranges are involved. Unless otherwise specified, the numerical ranges mentioned above are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form a range not explicitly stated.
[0047] Throughout this specification, references to "implementation," "partial implementation," "one implementation," "some implementations," "another implementation," "specific implementation," or "partial implementation" mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment.
[0048] I. Nitrogen-doped graphite materials This application provides a nitrogen-doped graphite material, the nitrogen-doped graphite material comprising graphite, wherein a nitrogen-doped carbon layer is disposed on the surface of the graphite; The nitrogen-doped graphite material has a crystallite size of La in the a-axis direction and a crystallite size of Lc in the c-axis direction, with 0.70≤La / Lc≤2.40.
[0049] The nitrogen-doped graphite material of this application improves the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries by controlling 0.70≤La / Lc≤2.40, while reducing the cyclic expansion of such electrochemical devices.
[0050] Specifically, when La / Lc is too small (<0.70), it indicates that the length La of the crystallites in the a-axis direction of the nitrogen-doped graphite material is insufficient relative to the thickness Lc in the c-axis direction. The nitrogen-doped graphite material tends to be isotropic, which is beneficial to reduce the lattice stress caused by anisotropic expansion during lithium ion insertion / extraction, thereby suppressing the cyclic expansion of the electrochemical device and improving the fast charging performance of the electrochemical device. However, a small La means that the graphite basal surface (i.e. the main active site for lithium ion storage) is not fully developed and the degree of graphitization is low, which leads to a decrease in the reversible capacity and compaction density of the nitrogen-doped graphite material, making it difficult to meet the high energy density requirements of the electrochemical device.
[0051] Conversely, when La / Lc is too large (>2.40), it indicates that the microcrystals of nitrogen-doped graphite material have grown excessively in the a-axis direction, and the graphite basal plane size La is significantly larger than the stack thickness Lc, exhibiting strong anisotropy. Although this is beneficial to improving the graphitization degree and lithium storage capacity of nitrogen-doped graphite material, thereby improving the reversible capacity and compaction density of nitrogen-doped graphite material, and thus improving the energy density of electrochemical device, during the lithium ion insertion / extraction process, the graphite sheets of nitrogen-doped graphite material undergo violent and uneven expansion along the c-axis direction, resulting in large internal stress and microcracks inside the particles of nitrogen-doped graphite material, which in turn significantly increases the cyclic expansion of electrochemical device. At the same time, an excessively large La will prolong the path of lithium ions diffusing from the particle edge to the deep interlayer, increase the lithium ion transport resistance, and deteriorate the fast charging performance of electrochemical device.
[0052] When the La / Lc ratio is controlled within the range of 0.70 to 2.40, on the one hand, a moderate amount of La ensures sufficient development of the graphite matrix, improving the graphitization degree and interlayer lithium storage capacity of nitrogen-doped graphite materials, thereby increasing the reversible capacity and compaction density of nitrogen-doped graphite materials, and consequently improving the energy density of electrochemical devices. On the other hand, a moderately restricted La ratio does not excessively dominate Lc, keeping the microcrystalline anisotropy of nitrogen-doped graphite materials at an acceptable level. This shortens the solid-phase diffusion distance of lithium ions (which is beneficial for lithium ion transport) and suppresses excessive volume expansion along the c-axis during lithium intercalation, thus significantly reducing the cycle expansion of electrochemical devices and improving their fast-charging performance. Therefore, this application achieves an excellent balance between energy density, fast-charging performance, and cycle expansion in electrochemical devices such as lithium-ion secondary batteries by precisely controlling the La / Lc ratio.
[0053] In some implementations, La / Lc can be 0.70, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, or 2.40, or fall within the range of any two of the above values.
[0054] In some implementations, 35nm ≤ La ≤ 60nm.
[0055] In some implementations, La can be 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, or 60nm, or fall within the range of any two of the above values.
[0056] In some implementations, 25nm ≤ Lc ≤ 45nm.
[0057] In some implementations, Lc can be 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm or 45nm, or within the range of any two of the above values.
[0058] In some implementations, 1.10 ≤ La / Lc ≤ 2.00.
[0059] In some embodiments, the full width at half maximum (FWHM) of the (110) crystal plane of the nitrogen-doped graphite material obtained by X-ray diffraction (XRD) is 0.16°-0.29°.
[0060] In some embodiments, the full width at half maximum (FWHM) of the (110) crystal plane obtained by X-ray diffraction (XRD) of the nitrogen-doped graphite material can be 0.160°, 0.161°, 0.162°, 0.163°, 0.164°, 0.165°, 0.166°, 0.167°, 0.168°, 0.169°, 0.170°, 0.171°, 0.172°, 0.173°, 0.174°, 0.175°, 0.176°, 0.177°, 0.178°, 0.179°, 0.180°, 0.181°, 0.182°, 0.183°, 0.184°, 0.185°, 0.186°, 0.187°, 0. 188°, 0.189°, 0.190°, 0.191°, 0.192°, 0.193°, 0.194°, 0.195°, 0.196°, 0.197°, 0.198°, 0.199°, 0.200°, 0.201°, 0.202°, 0.203°, 0.204°, 0.205° 0.206°, 0.207°, 0.208°, 0.209°, 0.210°, 0.211°, 0.212°, 0.213°, 0.214°, 0.215°, 0.216°, 0.217°, 0.218°, 0.219°, 0.220°, 0.221°, 0.222°, 0.2 23°, 0.224°, 0.225°, 0.226°, 0.227°, 0.228°, 0.229°, 0.230°, 0.231°, 0.232°, 0.233°, 0.234°, 0.235°, 0.236°, 0.237°, 0.238°, 0.239°, 0.240° 0.241°, 0.242°, 0.243°, 0.244°, 0.245°, 0.246°, 0.247°, 0.248°, 0.249°, 0.250°, 0.251°, 0.252°, 0.253°, 0.254°, 0.255°, 0.256°, 0.257°, 0.25 8°, 0.259°, 0.260°, 0.261°, 0.262°, 0.263°, 0.264°, 0.265°, 0.266°, 0.267°, 0.268°, 0.269°, 0.270°, 0.271°, 0.272°, 0.273°, 0.274°, 0.275°, 0.276°, 0.277°, 0.278°, 0.279°, 0.280°, 0.281°, 0.282°, 0.283°, 0.284°, 0.285°, 0.286°, 0.287°, 0.288°, 0.289°, or 0.290°, or within the range of any two of the above values.
[0061] In some embodiments, the full width at half maximum (FWHM) of the (002) crystal plane obtained by X-ray diffraction (XRD) of the nitrogen-doped graphite material is 0.17°-0.33°.
[0062] In some embodiments, the full width at half maximum (FWHM) of the (002) crystal plane obtained by X-ray diffraction (XRD) of the nitrogen-doped graphite material can be 0.170°, 0.171°, 0.172°, 0.173°, 0.174°, 0.175°, 0.176°, 0.177°, 0.178°, 0.179°, 0.180°, 0.181°, 0.182°, 0.183°, 0.184°, 0.185°, 0.186°, 0.187°, 0.188°, 0.189°, 0.190°, 0.191°, 0.192°, 0.193°, 0.194°, 0.195°, 0.196°, 0.197°, 0.19... 8°, 0.199°, 0.200°, 0.201°, 0.202°, 0.203°, 0.204°, 0.205°, 0.206°, 0.207°, 0.208°, 0.209°, 0.210°, 0.211°, 0.212°, 0.213°, 0.214°, 0.215°, 0. 216°, 0.217°, 0.218°, 0.219°, 0.220°, 0.221°, 0.222°, 0.223°, 0.224°, 0.225°, 0.226°, 0.227°, 0.228°, 0.229°, 0.230°, 0.231°, 0.232°, 0.233°, 0 0.234°, 0.235°, 0.236°, 0.237°, 0.238°, 0.239°, 0.240°, 0.241°, 0.242°, 0.243°, 0.244°, 0.245°, 0.246°, 0.247°, 0.248°, 0.249°, 0.250°, 0.251° 0.252°, 0.253°, 0.254°, 0.255°, 0.256°, 0.257°, 0.258°, 0.259°, 0.260°, 0.261°, 0.262°, 0.263°, 0.264°, 0.265°, 0.266°, 0.267°, 0.268°, 0.269° °, 0.270°, 0.271°, 0.272°, 0.273°, 0.274°, 0.275°, 0.276°, 0.277°, 0.278°, 0.279°, 0.280°, 0.281°, 0.282°, 0.283°, 0.284°, 0.285°, 0.286°, 0.2 87°, 0.288°, 0.289°, 0.290°, 0.291°, 0.292°, 0.293°, 0.294°, 0.295°, 0.296°, 0.297°, 0.298°, 0.299°, 0.300°, 0.301°, 0.302°, 0.303°, 0.304°, 0.The values are 305°, 0.306°, 0.307°, 0.308°, 0.309°, 0.310°, 0.311°, 0.312°, 0.313°, 0.314°, 0.315°, 0.316°, 0.317°, 0.318°, 0.319°, 0.320°, 0.321°, 0.322°, 0.323°, 0.324°, 0.325°, 0.326°, 0.327°, 0.328°, 0.329°, or 0.330°, or fall within the range of any two of the above values.
[0063] In some embodiments, the nitrogen element in the nitrogen-doped graphite material includes graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen. Based on the total mass of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen, the mass percentage of graphitic nitrogen is A, the mass percentage of pyridine nitrogen is B, and the mass percentage of pyrrole nitrogen is C, with 0.40 ≤ A / (B+C) ≤ 2.30.
[0064] In some implementations, A / (B+C) can be 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, or 0.85. 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1 0, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33, 1.34, 1.3 5, 1.36, 1.37, 1.38, 1.39, 1.40, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.50, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1. 60, 1.61, 1.62, 1.63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.70, 1.71, 1.72, 1.73, 1.74, 1.75, 1.76, 1.77, 1.78, 1.79, 1.80, 1.81, 1.82, 1.83, 1.84, 1 0.85, 1.86, 1.87, 1.88, 1.89, 1.90, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, 2.00, 2.01, 2.02, 2.03, 2.04, 2.05, 2.06, 2.07, 2.08, 2.09, 2.10, 2.11, 2.12, 2.13, 2.14, 2.15, 2.16, 2.17, 2.18, 2.19, 2.20, 2.21, 2.22, 2.23, 2.24, 2.25, 2.26, 2.27, 2.28, 2.29, or 2.30, or within the range of any two of the above values.
[0065] In some implementations, 0.90 ≤ A / (B+C) ≤ 1.75.
[0066] The introduction of graphitic nitrogen does not significantly disrupt the carbon six-membered ring structure between graphite layers in nitrogen-doped graphite materials, thus protecting the fast-charging performance of electrochemical devices and reducing cycle expansion. Pyrrole nitrogen and pyridine nitrogen can provide additional lithium storage sites, which is beneficial to improving the energy density of electrochemical devices. By controlling the range of values for A / (B+C), this application can further improve the energy density and fast-charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as further reduce the cycle expansion of electrochemical devices such as lithium-ion secondary batteries.
[0067] In some implementations, 0.25 ≤ A ≤ 0.75.
[0068] In some implementations, A can be 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, or 0. 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74 or 0.75, or within the range of any two of the above values.
[0069] In some implementations, 0.30 ≤ A ≤ 0.70.
[0070] In some implementations, 0.07 ≤ B ≤ 0.40.
[0071] In some implementations, B can be 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.40, or fall within the range of any two of the above values.
[0072] In some implementations, 0.10 ≤ B ≤ 0.35.
[0073] In some implementations, 0.07 ≤ C ≤ 0.40.
[0074] In some implementations, C can be 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.40, or fall within the range of any two of the above values.
[0075] In some implementations, 0.10 ≤ C ≤ 0.35.
[0076] In some embodiments, the average particle size Dv50 of the nitrogen-doped graphite material is D1, where 7 μm ≤ D1 ≤ 15 μm.
[0077] In some embodiments, the average particle size Dv50 of the nitrogen-doped graphite material is D1, which can be 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, or fall within the range of any two of the above values.
[0078] In some implementations, 8μm≤D1≤14μm.
[0079] In some implementations, 10μm≤D1≤12μm.
[0080] In some embodiments, the nitrogen-doped graphite material has an average thickness of D2, where 50 nm ≤ D2 ≤ 450 nm.
[0081] In some embodiments, the average thickness of the nitrogen-doped carbon layer in the nitrogen-doped graphite material is D2, which can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, or 450nm, or fall within the range of any two of the above values.
[0082] In some implementations, 100nm ≤ D2 ≤ 400nm.
[0083] In some implementations, 200nm ≤ D2 ≤ 360nm.
[0084] In some embodiments, the mass percentage of nitrogen is 0.01%-0.5% based on the mass of the nitrogen-doped graphite material.
[0085] In some embodiments, the mass percentage of nitrogen element, based on the mass of the nitrogen-doped graphite material, can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%. %, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, or 0.50%, or within the range of any two of the above values.
[0086] II. Electrodes This application provides an electrode comprising the nitrogen-doped graphite material described above.
[0087] In some embodiments, the electrode is a negative electrode.
[0088] In some embodiments, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.
[0089] In some embodiments, the negative current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is a copper foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.
[0090] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.
[0091] In some embodiments, the negative electrode active material layer includes the nitrogen-doped graphite material described above in this application.
[0092] In some embodiments, the negative electrode active material layer may also include at least one of other negative electrode active materials, negative electrode binders, and negative electrode conductive agents.
[0093] In some embodiments, other negative electrode active materials may include natural graphite, synthetic graphite, hard carbon, soft carbon, mesophase carbon microspheres (MCMB), Sn, SnO2, SnO, Li4Ti5O 12 The material is selected from at least one of LTO, Si material, silicon-carbon (Si-C) composite material, silicon-nitrogen (Si-N) composite material, and silicon-oxygen (Si-O) composite material. Other negative electrode active materials in this application are not limited to the above-mentioned materials, but also include other materials that can be used as negative electrode active materials for batteries.
[0094] In some embodiments, the negative electrode binder may include at least one of polyacrylic acid, polymethacrylic acid, polyacrylate, polymethacrylate, polyacrylamide, styrene-butadiene rubber (SBR), acrylic styrene-butadiene rubber, acrylic acid-acrylonitrile-acrylamide copolymer, acrylic acid-acrylonitrile-acrylate copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acryloyl rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, sodium carboxymethyl cellulose (CMC), hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, carboxymethyl chitosan, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester, polycarboxylic acid, polyurethane, alginate, fluorinated polymer, chlorinated polymer, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropylene. The negative electrode binder of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode binders.
[0095] In some embodiments, the negative electrode conductive agent may include at least one of carbon, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, activated carbon, and mesoporous carbon. The negative electrode conductive agent of this application is not limited to the above materials, but also includes other materials that can be used as battery negative electrode conductive agents.
[0096] III. Electrochemical Device This application provides an electrochemical device including the electrodes described above.
[0097] In this application, the electrochemical device includes any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy and vice versa. Specific, non-limiting examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.
[0098] In some embodiments, the electrochemical device also includes other electrodes, electrolytes, and membranes.
[0099] 1. Other electrodes In some implementations, the other electrodes are positive electrodes.
[0100] In some embodiments, the positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector.
[0101] In some embodiments, the positive current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is aluminum foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate. In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, activated carbon, and mesoporous carbon.
[0102] In some embodiments, the positive electrode active material layer may include a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.
[0103] In some embodiments, the positive electrode active material is selected from LiCoO2, LiNiO2, and LiNi x Mn y O2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co yAl z The group consisting of O2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4, LiMnPO4, and combinations thereof, wherein each x is independently 0.2 to 0.9; each y is independently 0.1 to 0.45; and each z is independently 0 to 0.2. The positive electrode active material of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as positive electrode active materials.
[0104] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride)-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polyvinyl butyral, polyvinylpyrrolidone (PVP), acrylic acid-acrylonitrile-acrylamide copolymer, and acrylic acid-acrylonitrile-acrylate copolymer. The positive electrode binder of this application is not limited to the above materials, but also includes other materials that can be used as battery positive electrode binders.
[0105] In some embodiments, the positive electrode conductive agent may include at least one of carbon, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, Super P, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, activated carbon, and mesoporous carbon. The positive electrode conductive agent in this application is not limited to the above materials, but also includes other materials that can be used as positive electrode conductive agents in batteries.
[0106] 2. Electrolytes In some embodiments, the electrolyte may include at least one of a gel electrolyte, a solid electrolyte, and a liquid electrolyte.
[0107] In some embodiments, the liquid electrolyte may include a non-aqueous solvent and a lithium salt.
[0108] In some embodiments, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate.
[0109] In some embodiments, the non-aqueous solvent may be at least one of carbonate compounds, carboxylic acid ester compounds, and ether compounds.
[0110] In some embodiments, the carbonate compound may include at least one of chain carbonate compounds, cyclic carbonate compounds, and fluorocarbonate compounds.
[0111] In some embodiments, the chain carbonate compound may include at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC).
[0112] In some embodiments, the cyclic carbonate compound may include at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), and vinylene carbonate (VC).
[0113] In some embodiments, the fluorocarbonate compound may include at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.
[0114] In some embodiments, the carboxylic acid ester compound may include at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate (PP), γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonate lactone, caprolactone, and methyl formate.
[0115] In some embodiments, the ether compound may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran.
[0116] In some embodiments, the non-aqueous solvent may also include at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.
[0117] 3. Diaphragm This application does not impose any particular limitation on the diaphragm, as long as it can achieve the purpose of this application. The diaphragm used in this application can be any diaphragm known in the prior art. For example, the type of diaphragm can include, but is not limited to, at least one of woven membranes, nonwoven membranes, microporous membranes, composite membranes, rolled membranes, and spun membranes. The material of the diaphragm can include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) mainly composed of polypropylene (PP), polyester, cellulose, polyimide (PI), polyamide (PA), spandex, and aramid. Polyester can include, but is not limited to, polyethylene terephthalate (PET) film.
[0118] In some embodiments, the diaphragm includes a substrate layer. The substrate layer may include, but is not limited to, at least one of a nonwoven fabric, membrane, or composite membrane having a porous structure. The material of the substrate layer may include, but is not limited to, at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. In some embodiments, the substrate layer may include, but is not limited to, at least one of a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane.
[0119] In some embodiments, the diaphragm further includes a surface treatment layer disposed on at least one surface of the substrate layer. The surface treatment layer may include, but is not limited to, at least one of a polymer layer, an inorganic layer, and a layer formed by a mixture of polymers and inorganic substances. The polymer layer includes polymers. This application does not particularly limit the polymer, as long as it achieves the purpose of this application. For example, the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene). The inorganic layer includes inorganic particles and a binder. This application does not particularly limit the inorganic particles and binder, as long as they achieve the purpose of this application. For example, the inorganic particles may include, but are not limited to, at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. For example, the adhesive may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride)-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polyvinyl butyral, polyvinylpyrrolidone (PVP), acrylic acid-acrylonitrile-acrylamide copolymer, and acrylic acid-acrylonitrile-acrylate copolymer.
[0120] In some embodiments, the present application does not have a particular limitation on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm is from 1 μm to 500 μm.
[0121] IV. Electronic Devices This application also provides an electronic device that includes the electrochemical device described above.
[0122] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. The electrochemical device described in this application is also not particularly limited in its use and can be used in any electronic device known in the prior art. According to some embodiments of this application, the electronic device includes, but is not limited to, mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, and android robots.
[0123] V. Testing Methods 1. Testing of La and Lc in nitrogen-doped graphite materials The crystal structure of nitrogen-doped graphite was analyzed using an X-ray diffractometer with a scanning range of 10-80° (2θ) to obtain the full width at half maximum (FWHM) information. Based on the FWHM of the (100) plane diffraction peak, the crystallite size La in the a-axis direction of the nitrogen-doped graphite was calculated using the Scherrer Equation; based on the FWHM of the (002) plane diffraction peak, the crystallite size Lc in the c-axis direction of the nitrogen-doped graphite was calculated using the Scherrer Equation. The Scherrer Equation is shown below: La=Kλ / (β 110 ×cosθ 110 ); Lc=Kλ / (β 002 ×cosθ 002 ); Where K=0.89, λ=0.15418nm, and β is the half-maximum width in radians.
[0124] 2. Full width at half maximum (FWHM) measurements of (110) and (002) crystal planes in nitrogen-doped graphite materials The crystal structure of nitrogen-doped graphite materials can be analyzed using an X-ray diffractometer with a scanning range of 10-80° (2θ) to obtain the full width at half maximum (FWHM) data of the (110) and (002) crystal planes of nitrogen-doped graphite materials.
[0125] 3. Test of the mass ratio of graphitic nitrogen, pyridine nitrogen and pyrrole nitrogen in nitrogen-doped graphite materials X-ray photoelectron spectroscopy (XPS) was used to test nitrogen-doped graphite materials, obtaining high-resolution N1s spectra. Then, peak fitting was performed on the N1s spectra, and the speciation of nitrogen was assigned based on the binding energy to obtain the peak areas of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen. Specifically, graphitic nitrogen was located at 401.3 ± 0.2 eV, pyridine nitrogen at 398.6 ± 0.2 eV, and pyrrole nitrogen at 400.3 ± 0.2 eV. Finally, the mass percentages of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen were calculated using the following formula based on their respective peak areas: The mass percentage of graphite nitrogen A = peak area of graphite nitrogen / (peak area of graphite nitrogen + peak area of pyridine nitrogen + peak area of pyrrole nitrogen); The mass percentage of pyridine nitrogen, B = peak area of pyridine nitrogen / (peak area of graphite nitrogen + peak area of pyridine nitrogen + peak area of pyrrole nitrogen); The mass percentage of pyrrole nitrogen, C = peak area of pyrrole nitrogen / (peak area of graphite nitrogen + peak area of pyridine nitrogen + peak area of pyrrole nitrogen).
[0126] 4. Test of average particle size Dv50 of nitrogen-doped graphite materials or graphite The average particle size Dv50 of nitrogen-doped graphite materials or graphite was determined using a Malvern Mastersizer 3000 laser particle size analyzer. The specific testing steps are as follows: Take 0.1–0.5 g of nitrogen-doped graphite material or graphite powder sample and add it to 50–100 mL of a dispersant solution (such as sodium hexametaphosphate or sodium dodecylbenzenesulfonate) containing 0.1–0.2% by mass (solvent: deionized water or anhydrous ethanol). Disperse the sample using ultrasonication for 5–15 min to ensure thorough particle dispersion and a uniform suspension. Inject the suspension into the sample cell of the laser particle size analyzer and perform particle size distribution testing using the wet method. The instrument automatically records the volume-based particle size distribution curve. The particle size value corresponding to a cumulative volume fraction of 50% in the particle group is read, which is the average particle size Dv50 of the nitrogen-doped graphite material or graphite.
[0127] 5. Measurement of the average thickness of nitrogen-doped carbon layer in nitrogen-doped graphite materials The average thickness of the nitrogen-doped carbon layer in nitrogen-doped graphite material was determined using a JEM-2100F transmission electron microscope (TEM). A total of 25 nitrogen-doped graphite particles were tested, and the nitrogen-doped carbon layer data at 5 different locations were measured for each particle. The arithmetic mean of all measurements was calculated as the average thickness of the nitrogen-doped carbon layer in the nitrogen-doped graphite material.
[0128] 6. Mass percentage test of embedded structure, lamellar structure and fibrous structure in graphite raw material coke Polarizing microscopes utilize the differences in the reflection of polarized light by graphite microcrystals with different orientations in graphite raw material coke (petroleum coke and / or pitch coke and / or needle coke) to transform microscopic crystallographic orientation information into visible contrasts of brightness and color, thereby intuitively characterizing the structural order of graphite raw material coke. The structural order of graphite raw material coke, from low to high, is successively manifested as mosaic structure, sheet structure and fibrous structure.
[0129] The graphite raw material coke (petroleum coke and / or pitch coke and / or needle coke) was tested using a polarizing microscope, and the mosaic structure, lamellar structure and fibrous structure in the graphite raw material coke were quantitatively analyzed. The mass percentage of each of the mosaic structure, lamellar structure and fibrous structure in the graphite raw material coke can be obtained, and the sum of the mass percentages of each of the mosaic structure, lamellar structure and fibrous structure is 100%.
[0130] 7. Energy density test (1) Preparation of the working electrode: The nitrogen-doped graphite material to be tested, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) binder were mixed evenly in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1 to form a slurry. The slurry was then uniformly coated onto a copper foil current collector and vacuum dried at 120°C for 12 h. The slurry was then cut into discs with a diameter of 14 mm to serve as the working electrode. The areal loading of the active material (nitrogen-doped graphite material) on the discs (working electrode) was 2.0 mg / cm². 2 ; (2) Counter electrode and reference electrode: Lithium metal sheets are used as the counter electrode and reference electrode, respectively; (3) Electrolyte and membrane: The electrolyte is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) containing 1 M LiPF6 (the volume ratio of EC to DMC is 1:1), and the membrane is a Celgard 2400 polypropylene membrane. (4) Battery assembly: In a glove box filled with argon (water oxygen content <0.1 ppm), the working electrode, counter electrode, reference electrode, electrolyte and separator are assembled into a CR2032 coin cell. (5) Test Procedure: Under a constant temperature environment of 25℃, the five assembled CR2032 coin cells were first left to stand for 2 hours. Then, the following charge and discharge steps were performed sequentially: First, discharge at a constant current of 0.05C until the voltage reaches 5 mV, and let stand for 5 minutes; then continue to discharge at a constant current of 0.05 mA until 5 mV, and let stand for 5 minutes again; finally, charge at a constant current of 0.1C to 2.0 V, and record the charging capacity at this point as the 0.1C charging specific capacity. The above experiment was repeated for each CR2032 coin cell, i.e., the experiment was repeated 5 times. The average value of the 0.1C charging specific capacity was taken, and the specific capacity of the negative electrode was calculated according to the following formula: Negative electrode specific capacity (mAh / g) = average value of specific capacity at 0.1C charge (unit: mAh) / mass of negative electrode material (unit: g); The mass of the negative electrode material refers to the mass of the nitrogen-doped graphite material, the negative electrode active material of this application. The acceptable standard for the specific capacity of the negative electrode is ≥333.0mAh / g, and the excellent standard is ≥345.0mAh / g; The larger the specific capacity of the negative electrode, the higher the energy density of the lithium-ion secondary battery under the same design.
[0131] 8. Fast charging performance test ① In a 25℃ environment, discharge the lithium-ion secondary battery at a constant current of 0.2C to 3.0V, let it rest for 10 minutes, then charge it at a constant current and constant voltage of 0.5C to 4.52V, let it rest for 10 minutes, then discharge it at a constant current of 0.5C to 3.0V, let it rest for 10 minutes, and record the discharge capacity at this time, which is recorded as the initial capacity P1; ② Subsequently, charge it at a constant current and constant voltage of 5C to 4.52V, cut off the current at 0.05C, and let it rest for 10 minutes; ③ Then discharge it at a constant current of 0.5C to 3.0V, and let it rest for 10 minutes; then repeat steps ② and ③ for 50 cycles, and record the discharge capacity at this time, which is recorded as the discharge capacity P2 after 50 cycles. Finally, calculate the capacity retention rate (%) of the lithium-ion secondary battery according to the following formula: Capacity retention rate (%) = 100% × P2 / P1; The pass standard for capacity retention is ≥80.0%, and the excellent standard is ≥90.0%. The higher the capacity retention rate (%), the higher the fast charging performance of the lithium-ion secondary battery under the same design.
[0132] 9. Cyclic Expansion Test ① In a 25℃ environment, the lithium-ion secondary battery was discharged at a constant current of 0.2C to 3.0V, rested for 10 minutes, then charged at a constant current and constant voltage of 0.5C to 4.52V, rested for 10 minutes, and the thickness T1 of the lithium-ion secondary battery was recorded at this time. Then, it was discharged at a constant current of 0.5C to 3.0V and rested for 10 minutes; ② Subsequently, it was charged at a constant current and constant voltage of 3C to 4.20V, with a cutoff current of 2.2C, and then charged at a constant current and constant voltage of 2.2C to 4.30V, with a cutoff current of 1.65C. Charge the battery to 4.40V at a constant current and constant voltage of 1.65C, with a cutoff current of 1.2C. Then charge it to 4.52V at a constant current and constant voltage of 1.2C, with a cutoff current of 0.05C, and let it rest for 10 minutes. Next, discharge the battery to 3.0V at a constant current of 0.5C and let it rest for 10 minutes. Repeat steps ② and ③ 1000 times. Then charge the lithium-ion secondary battery to full charge as in step ②. Record the thickness T2 of the lithium-ion secondary battery at this time, and calculate the thickness expansion rate (%) of the lithium-ion secondary battery according to the following formula: Thickness expansion rate (%) = 100% × (T2 - T1) / T1; The acceptable standard for thickness expansion rate is ≤14.0%, and the excellent standard is ≤11.5%; The smaller the thickness expansion rate (%), the lower the cycle expansion of the lithium-ion secondary battery under the same design.
[0133] VI. Examples It should be noted that, in the specific embodiments of this application, lithium-ion secondary batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion secondary batteries.
[0134] Unless otherwise specified, all reagents, materials, and instruments used in the following examples and comparative examples are commercially available. Furthermore, unless otherwise specified, "parts" and "%" refer to mass measurements.
[0135] In the following examples and comparative examples, the use of some reagents and materials is as follows: Petroleum coke, purchased from China Petroleum & Chemical Corporation; Pitch coke, purchased from Baowu Carbon Industry Technology Co., Ltd.; Needle coke, purchased from Shandong Lianhua New Materials Co., Ltd.; High-temperature asphalt, oil-coated asphalt 250#, purchased from Xinjiang Zhongtan New Material Technology Co., Ltd.; Packaging bags, aluminum-plastic film, E103, Shanghai Zijang New Material Technology Co., Ltd.; The diaphragm is made of polyethylene with a thickness of 5μm, manufactured by Shenzhen Xingyuan Material Technology Co., Ltd. Polyvinylidene fluoride (PVDF), 768739, McLean; Ethylene carbonate (EC), CAS No.: 96-49-1; Diethyl carbonate (DEC), CAS No.: 105-58-8; Propylene carbonate (PC), CAS No.: 108-32-7; Propyl propionate (PP), CAS No.: 106-36-5; Vinyl carbonate (VC), CAS No.: 872-36-6.
[0136] Example 1 This embodiment provides a nitrogen-doped graphite material, which includes graphite and has a nitrogen-doped carbon layer disposed on its surface; The nitrogen-doped graphite material has a crystallite size of La in the a-axis direction, La=54nm, and a crystallite size of Lc in the c-axis direction, Lc=36nm, with La / Lc=1.50. The nitrogen-doped graphite material obtained by X-ray diffraction (XRD) has a full width at half maximum (FWHM) of F1 for the (110) crystal plane, F1 = 0.1865° (approximately 0.003255 rad), and a full width at half maximum (FWHM) of F2 for the (002) crystal plane, F2 = 0.2243° (approximately 0.0039148 rad). The nitrogen in the nitrogen-doped graphite material includes graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen. Based on the total mass of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen, the mass percentage of graphitic nitrogen is A, A=0.57, the mass percentage of pyridine nitrogen is B, B=0.25, and the mass percentage of pyrrole nitrogen is C, C=0.18. A / (B+C)=1.33. The average particle size Dv50 of the nitrogen-doped graphite material is D1, where D1 = 10 μm, and the average thickness of the nitrogen-doped carbon layer in the nitrogen-doped graphite material is D2, where D2 = 360 nm. Based on the mass of the nitrogen-doped graphite material, the mass percentage of nitrogen is g%, g=0.3.
[0137] The preparation method of the above-mentioned nitrogen-doped graphite material includes the following steps: S1. Take petroleum coke, pitch coke and needle coke in a mass ratio of 6:5:9, crush and mix them to obtain a graphite raw material coke mixture. At this time, the test by polarizing light microscope shows that in the graphite raw material coke mixture, the mass proportion of the mosaic structure is 20%, the mass proportion of the sheet structure is 15%, and the mass proportion of the fibrous structure is 65%. S2. The graphite raw material coke mixture obtained in step S1 is mixed with high-temperature pitch at a mass ratio of 1:0.15. Then, it is placed in a vertical high-temperature granulation kettle, granulated at 650°C, kept at the temperature for 3 hours, cooled down and removed from the furnace, and then mixed to obtain graphite precursor powder. S3. The graphite precursor powder obtained in step S2 is subjected to graphitization treatment at 3000℃. After graphitization, it is screened to obtain graphite with an average particle size Dv50 of 9.64μm. S4. Mix the graphite, nitrogen source pyridine, ferric nitrate, and carbon source glucose obtained in step S3 in a mass ratio of 1:0.08:0.02:0.08, place them in a box furnace, heat treat at 950℃ for 4 hours, cool to room temperature, and demagnetize to obtain nitrogen-doped graphite material with an average particle size Dv50=10μm.
[0138] This embodiment also provides a lithium-ion secondary battery (electrochemical device), the preparation method of which includes the following steps: 1. Preparation of negative electrode sheet Nitrogen-doped graphite material, sodium carboxymethyl cellulose (CMC) anode binder, and styrene-butadiene rubber (SBR) anode binder were mixed at a mass ratio of 97.7:1.1:1.2. Deionized water was added, and the mixture was stirred evenly under vacuum to obtain a negative electrode active material slurry with a solid content of 50 wt%. Copper foil (8 μm) was used as the negative electrode current collector, and the negative electrode active material slurry was uniformly coated on both sides of the current collector. After drying, cold pressing, and slitting, a negative electrode sheet was obtained, with a single-sided thickness of 50 μm for the negative electrode active material layer.
[0139] 2. Preparation of the positive electrode sheet The positive electrode active material (lithium cobalt oxide, LiCoO2), positive electrode conductive agent (Super P), and positive electrode binder (polyvinylidene fluoride, PVDF) were mixed at a mass ratio of 97.6:1.1:1.3. N-methylpyrrolidone (NMP) was added, and the mixture was stirred evenly under vacuum to obtain a positive electrode active material slurry with a solid content of 62 wt%. Aluminum foil (10 μm) was used as the positive electrode current collector, and the positive electrode active material slurry was uniformly coated on both sides of the current collector. After drying, cold pressing, and slitting, the positive electrode sheet was obtained, with a single-sided thickness of 42 μm for the positive electrode active material layer.
[0140] 3. Preparation of electrolyte In a dry argon atmosphere glove box, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) were mixed in a mass ratio of EC:DEC:PC:PP:VC = 25:25:15:31:4 to obtain a non-aqueous solvent. Then, lithium salt LiPF6 was added to dissolve and mix thoroughly to obtain an electrolyte; wherein the mass concentration of LiPF6 in the electrolyte was 8%.
[0141] 4. Preparation of lithium-ion secondary batteries (electrochemical devices) The positive electrode, separator, and negative electrode prepared above are stacked in sequence and wound to obtain an electrode assembly. The electrode assembly is placed in a packaging bag (aluminum-plastic film), dried, and then injected with electrolyte. After vacuum sealing, settling, formation, degassing, and edge trimming, a lithium-ion secondary battery is obtained.
[0142] Examples 2-6 and Comparative Examples 1-2 Examples 2-6 and Comparative Examples 1-2 differ from Example 1 in that the values of La, Lc, F1, and F2 are different, as shown in Table 1. All other values are the same as in Example 1. The mass ratios of petroleum coke, pitch coke, and needle coke in step S1 are adjusted to control the mass proportions of the embedded, sheet-like, and fibrous structures in the graphite raw material coke mixture, thereby achieving the values of La, Lc, F1, and F2 in the nitrogen-doped graphite material as shown in Table 1.
[0143] Examples 7-11 Examples 7-11 differ from Example 1 in that the values of A, B, and C are different, as shown in Table 2. All other values are the same as in Example 1. Maintaining the mass ratio of graphite, nitrogen source pyridine, and carbon source glucose in step S4, the relative contents of graphite nitrogen, pyridine nitrogen, and pyrrole nitrogen in the nitrogen-doped carbon layer are controlled by adjusting the mass ratio of graphite and ferric nitrate (i.e., changing the amount of ferric nitrate) and the heat treatment temperature and time. This results in the values of A, B, C, and A / (B+C) of the nitrogen-doped graphite material as shown in Table 2, and maintains the mass percentage (g%) of nitrogen in the nitrogen-doped graphite material unchanged.
[0144] Examples 12-14 Examples 12-14 differ from Example 1 in that the values of D1, La, Lc, F1, and F2 are different, as shown in Table 3. All other parameters are the same as in Example 1. Graphite with different average particle sizes (Dv50) was obtained by adjusting the sieving in step S3, thus resulting in the values of D1, La, Lc, F1, and F2 as shown in Table 3. Changes in D1 lead to changes in F1 and F2, thereby affecting La and Lc. Simultaneously, the parameters D2, g, A, B, and C were kept constant by adjusting the mass ratio of graphite, nitrogen source pyridine, ferric nitrate, and carbon source glucose.
[0145] Examples 15-17 Examples 15-17 differ from Example 1 in that the value of D2 is different, as shown in Table 4. All other parameters are the same as in Example 1. The mass ratios of graphite, nitrogen source pyridine, ferric nitrate, and carbon source glucose in step S4 were adjusted to achieve the D2 values shown in Table 4, while keeping parameters such as g, A, B, and C constant. Changes in the D2 value do not affect the values of La, Lc, F1, and F2.
[0146] Comparative Example 3 This comparative example provides a carbon-doped graphite material, which differs from the nitrogen-doped graphite material of Example 1 in that a carbon layer is disposed on the graphite surface instead of a nitrogen-doped carbon layer, as detailed below: The carbon-doped graphite material includes graphite, and a carbon layer (nitrogen-free) is disposed on the surface of the graphite. The carbon-doped graphite material has a crystallite size of La' in the a-axis direction, La'=54nm, and a crystallite size of Lc' in the c-axis direction, Lc'=36nm, with La' / Lc'=1.50; The carbon-doped graphite material obtained by X-ray diffraction (XRD) has a full width at half maximum (FWHM) of F1' for the (110) crystal plane, F1' = 0.1865° (approximately 0.003255 rad), and a full width at half maximum (FWHM) of F2' for the (002) crystal plane, F2' = 0.2243° (approximately 0.0039148 rad). The average particle size Dv50 of the carbon-doped graphite material is D1', where D1' = 10 μm, and the average thickness of the carbon layer (excluding nitrogen) in the carbon-doped graphite material is D2', where D2' = 360 nm.
[0147] The preparation method of the above-mentioned carbon-doped graphite material includes the following steps: S1. Take petroleum coke, pitch coke and needle coke in a mass ratio of 6:5:9, crush and mix them to obtain a graphite raw material coke mixture. At this time, the test by polarizing light microscope shows that in the graphite raw material coke mixture, the mass proportion of the mosaic structure is 20%, the mass proportion of the sheet structure is 15%, and the mass proportion of the fibrous structure is 65%. S2. The graphite raw material coke mixture obtained in step S1 is mixed with high-temperature pitch at a mass ratio of 1:0.15. Then, it is placed in a vertical high-temperature granulation kettle, granulated at 650°C, kept at the temperature for 3 hours, cooled down and removed from the furnace, and then mixed to obtain graphite precursor powder. S3. The graphite precursor powder obtained in step S2 is subjected to graphitization treatment at 3000℃. After graphitization, it is screened to obtain graphite with an average particle size Dv50 of 9.64μm. S4. Mix the graphite and carbon source glucose obtained in step S3 at a mass ratio of 1:0.16, place them in a box furnace, heat treat at 950℃ for 4 hours, cool to room temperature, and demagnetize to obtain carbon-doped graphite material with an average particle size Dv50=10μm.
[0148] This comparative example also provides a lithium-ion secondary battery (electrochemical device), the preparation method of which is described in Example 1.
[0149] Table 1. Condition parameters and performance test results for Examples 1-6 and Comparative Examples 1-2 As shown in Table 1, the nitrogen-doped graphite material of this application can simultaneously improve the energy density and fast charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of electrochemical devices such as lithium-ion secondary batteries.
[0150] Table 2. Condition parameters and performance test results for Examples 1 and 7-11 As shown in Table 2, the nitrogen-doped graphite material of this application can simultaneously improve the energy density and fast charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of electrochemical devices such as lithium-ion secondary batteries.
[0151] Table 3. Condition parameters and performance test results for Examples 1, 12-14 As shown in Table 3, the nitrogen-doped graphite material of this application can simultaneously improve the energy density and fast charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of electrochemical devices such as lithium-ion secondary batteries.
[0152] Table 4. Condition parameters and performance test results for Examples 1 and 15-17 As shown in Table 4, the nitrogen-doped graphite material of this application can simultaneously improve the energy density and fast charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of electrochemical devices such as lithium-ion secondary batteries.
[0153] Table 5. Condition parameters and performance test results of Example 1 and Comparative Example 3 As shown in Table 5, the nitrogen-doped graphite material of this application can simultaneously improve the energy density and fast charging performance of electrochemical devices such as lithium-ion secondary batteries, as well as reduce the cyclic expansion of electrochemical devices such as lithium-ion secondary batteries.
[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.
Claims
1. A nitrogen-doped graphite material, characterized in that, The nitrogen-doped graphite material includes graphite, and a nitrogen-doped carbon layer is disposed on the surface of the graphite. The nitrogen-doped graphite material has a crystallite size of La in the a-axis direction and a crystallite size of Lc in the c-axis direction, with 0.70≤La / Lc≤2.
40.
2. The nitrogen-doped graphite material as described in claim 1, characterized in that, Satisfy at least one of the following (1)-(3): (1) 35nm≤La≤60nm; (2) 25nm≤Lc≤45nm; (3) 1.10≤La / Lc≤2.
00.
3. The nitrogen-doped graphite material as described in claim 1, characterized in that, Satisfy at least one of the following (1)-(2): (1) The full width at half maximum (FWHM) of the (110) crystal plane of the nitrogen-doped graphite material obtained by X-ray diffraction is 0.16°-0.29°; (2) The full width at half maximum (FWHM) of the (002) crystal plane obtained by X-ray diffraction of the nitrogen-doped graphite material is 0.17°-0.33°.
4. The nitrogen-doped graphite material as described in claim 1, characterized in that, The nitrogen in the nitrogen-doped graphite material includes graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen. Based on the total mass of graphitic nitrogen, pyridine nitrogen, and pyrrole nitrogen, the mass percentage of graphitic nitrogen is A, the mass percentage of pyridine nitrogen is B, and the mass percentage of pyrrole nitrogen is C, with 0.40 ≤ A / (B+C) ≤ 2.
30.
5. The nitrogen-doped graphite material as described in claim 4, characterized in that, Satisfy at least one of the following (1)-(4): (1)0.25≤A≤0.75; (2)0.07≤B≤0.40; (3)0.07≤C≤0.40; (4) 0.90≤A / (B+C)≤1.
75.
6. The nitrogen-doped graphite material as described in claim 1, characterized in that, Satisfy at least one of the following (1)-(3): (1) The average particle size Dv50 of the nitrogen-doped graphite material is D1, 7μm≤D1≤15μm; (2) In the nitrogen-doped graphite material, the average thickness of the nitrogen-doped carbon layer is D2, 50nm≤D2≤450nm; (3) In some embodiments, the mass percentage of nitrogen element is 0.01%-0.5% based on the mass of the nitrogen-doped graphite material.
7. The nitrogen-doped graphite material as described in claim 6, characterized in that, Satisfy at least one of the following (1)-(2): (1) 10μm≤D1≤12μm; (2) 200nm≤D2≤360nm.
8. An electrode, characterized in that, Includes the nitrogen-doped graphite material as described in any one of claims 1-7.
9. An electrochemical device, characterized in that, Includes the electrode as described in claim 8.
10. An electronic device, characterized in that, Including the electrochemical device as described in claim 9.
